INFLUENCE OF ZINC CHLORIDE INTRAGASTRIC AND PARENTERAL ADMINISTRATION ON SYSTEMIC HEMODYNAMICS IN A CHANGING CALCIUM HOMEOSTASIS - D. H. OGANESYAN; V. B. BRIN; O. T. KABISOV (Кубанский научный медицинский вестник)
The objective of the research work is to study the influence of altered calcium homeostasis on the hemodynamic effects of zinc chloride. The experimental hypercalcaemiawas created in Wistar rats by intragastric administration of calcium chloride. Zinc chloride was administered intragastrically via a probe and subcutaneously, at a dose of 20 mg /kg daily for one month. At the end of the experiment the functional state of the cardiovascular system was investigated, the basic parameters of systemic hemodynamics were determined. The following parameters were determined: blood pressure – invasively (bloody way) by introducing a plastic catheter into the femoral artery. For measuring a minute volume of blood thermistor was inserted through the left common carotid artery to the aortic arch. Indications were recorded on the MX-04 monitor. Mean arterial pressure was calculated by a special formula, heart rate –by means of a surgical monitor; cardiac index, stroke index and the specific peripheral vascular resistance were calculated by special formulas. Studies have shown that in subcutaneous and intragastric administration changes in systemic hemodynamics in the form of hypertension was observed. In the experimental hypercalcaemia, induced by administration of calcium chloride, metal intragastric administration produced significantly less hypertensive reaction. In the group with subcutaneous administration of metal on the background of hypercalcaemia the changes were not pronounced.